PENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA MATERI MELAKUKAN OPERASI HITUNG BILANGAN SAMPAI TIGA ANGKA MELALUI PEMBELAJARAN KOLABORATIF PADA SISWA KELAS III SD NEGERI 1 SELATPANJANG TAHUN PELAJARAN 2019/2020 - Aisyah, Aisyah (JGK (Jurnal Guru Kita), 2019)
Abstract: Increase Student Motivation and Learning Achievement in Mathematics Learning Materials Perform Number Count Operation Up to Three Numbers Through Collaborative Learning in Third Grade Students of Grade 1 Selatpanjang School Year 2019/2020. The purpose of this study is to find out the increased motivation and math learning results of grade III sdn 1 Straits students through collaborative model learning on the material of performing number counting operations up to three numbers. This research is classroom action research. Research is conducted in two cycles, with each cycle consisting of planning, observation, evaluation, analysis, and reflection. The subject of the study in the implementation of class action research was conducted in grade III SDN 1 SelatpanjangTahun Pelajaran 2019/2020 with the number of students as many as 15 children consisting of 5 male students and 10 female students. Data collection techniques and tools are observing, testing and documentation. Data analysis is usedqualitative analysis techniques. The results were motivated and the results of learning to increase in each cycle, which is the motivation of the initial study of only 6 students or 40% to 11 students or 73.333% in the first cycle and the last cycle of only 93.33% or 14 students, as well as the average student learning achievement in the initial condition only 59.97 in the initial study, to 68.07 in the first cycle and 77.83 in the last cycle, as well as an increase in completion of 8 students or 53.33% and in cycle II increased back to 14 students or 93.33%, and all indicators and criteria of success have been achieved, so that the implementation of learning improvements is declared complete and completed in the second cycle. Based on the results of the research carried out can be concluded that the implementation of collaborative learning models can improve the motivation and learning performance of grade III students of SDN 1 Selat panjangTahun Pelajaran 2019/2020 on mathematics learning in the material of performing number counting operations up to three numbers. Keywords: Motivation, Achievement, Collaborative Abstrak: Peningkatkan Motivasi Dan Prestasi Belajar Siswa Pada Pembelajaran Matematika Materi Melakukan Operasi Hitung Bilangan Sampai Tiga Angka Melalui Pembelajaran Kolaboratif Pada Siswa Kelas Iii Sd Negeri 1 Selatpanjang Tahun Pelajaran 2019/2020. Tujuan penelitian ini adalah untuk mengetahui peningkatan motivasi dan hasil belajar matematika siswa kelas III SDN 1 Selat panjang melalui pembelajaran model kolaboratif pada materi melakukan operasi hitung bilangan sampai tiga angka. Penelitian ini merupakan penelitian tindakan kelas (classroom action research). Penelitian dilaksanakan dalam dua siklus, dengan tiap siklus terdiri atas perencanaan, observasi, evaluasi, analisis, dan refleksi. Subjek penelitian dalam pelaksanaan penelitian tindakan kelas ini dilaksanakan di kelas III SDN 1 SelatpanjangTahun Pelajaran 2019/2020 dengan jumlah siswa sebanyak 15 anak terdiri dari 5 siswa laki-laki dan 10 siswa perempuan. Teknik dan alatpengumpulan data adalahobservasi, tes dan dokumentasi. Analisis data digunakanteknikanalisiskualitatif. Hasil penelitiandiperolehmotivasi dan hasilbelajarmeningkat pada setiapsiklusnya, yaitumotivasi dari studi awal hanya 6 siswaatau 40% menjadi 11 siswaatau 73,333% pada sikluspertama dan siklusterakhirsebesar 93,33% atau 14 siswa, sertaprestasi hasil belajar siswa rata-rata pada kondisi awal hanya 59,97 pada studiawal, menjadi 68,07 pada sikluspertama dan 77,83 pada siklusterakhir, sertapeningkatanketuntasandari 8 siswaatau 53,33% dan pada siklus II meningkatkembalimenjadi 14 siswaatau 93,33%, dan semua indikator dan kriteria keberhasilan telah tercapai, sehingga pelaksanaan perbaikan pembelajaran dinyatakan selesai dan tuntas pada siklus kedua.Berdasarkanhasilpenelitian yang dilaksanakan dapat disimpulkan bahwa penerapan model pembelajaran kolaboratif dapat meningkatkan motivasi dan prestasi belajarsiswa kelas III SDN 1 Selat panjangTahun Pelajaran 2019/2020 pada pembelajaran matematika pada materi melakukan operasi hitung bilangan sampai tiga angka. Kata Kunci: Motivasi, Prestasi, Kolaboratif